Horizontal and vertical velocities derived from the IDS contribution to ITRF2014, and comparisons with geophysical models. Issue 1 (19th July 2016) - Moreaux, G.; Lemoine, F.G.; Argus, D.F.; Santamaría-Gómez, A.; Willis, P.; Soudarin, L.; Gravelle, M.; Ferrage, P.
Abstract: In the context of the 2014 realization of the International Terrestrial Reference Frame, the International DORIS (Doppler Orbitography Radiopositioning Integrated by Satellite) Service (IDS) has delivered to the IERS a set of 1140 weekly SINEX files including station coordinates and Earth orientation parameters, covering the time period from 1993.0 to 2015.0. From this set of weekly SINEX files, the IDS combination centre estimated a cumulative DORIS position and velocity solution to obtain mean horizontal and vertical motion of 160 stations at 71 DORIS sites. The main objective of this study is to validate the velocities of the DORIS sites by comparison with external models or time-series. Horizontal velocities are compared with two recent global plate models (GEODVEL 2010 and NNR-MORVEL56). Prior to the comparisons, DORIS horizontal velocities were corrected for Global Isostatic Adjustment from the ICE-6G (VM5a) model. For more than half of the sites, the DORIS horizontal velocities differ from the global plate models by less than 2–3 mm yr −1 . For five of the sites (Arequipa, Dionysos/Gavdos, Manila and Santiago) with horizontal velocity differences with respect to these models larger than 10 mm yr −1, comparisons with GNSS estimates show the veracity of the DORIS motions. Vertical motions from the DORIS cumulative solution are compared with the vertical velocities derived from the latest GPS cumulative solution over the time span 1995.0–2014.0 from the University of La Rochelle solution at 31 co-located DORIS-GPS sites. These two sets of vertical velocities show a correlation coefficient of 0.83. Vertical differences are larger than 2 mm yr −1 at 23 percent of the sites. At Thule, the disagreement is explained by fine-tuned DORIS discontinuities in line with the mass variations of outlet glaciers. Furthermore, the time evolution of the vertical time-series from the DORIS station in Thule show similar trends to the GRACE equivalent water height.